2011
DOI: 10.1021/je101344v
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of CO2in Alcohols, Glycols, Ethers, and Ketones at High Pressures from (288.15 to 318.15) K

Abstract: The constant-volume method is used to determine the solubility of CO 2 in methanol, ethanol, n-propanol, n-butanol, n-propanol, ethylene glycol, propylene glycol, acetone, 2-butanone, ethylene glycol monomethyl ether, and ethylene glycol monoethyl ether under the pressure of 6 MPa and the temperature variations from (288.15 to 318.15) K in this paper. It is found by contrast that ketones have a greater ability to dissolve CO 2 than alcohols, ethers, and glycols, which also indicate that both the carbonyl group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 22 publications
6
88
0
Order By: Relevance
“…Ethylene glycol (EG) is an organic solvent which is used as an antifreeze, a heat transfer fluid, a precursor of polymers and which is envisaged for CO2 absorption [1,2]. Besides many other applications, this solvent is used as entrainer for the separation of waterethanol mixtures by means of extractive distillation [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene glycol (EG) is an organic solvent which is used as an antifreeze, a heat transfer fluid, a precursor of polymers and which is envisaged for CO2 absorption [1,2]. Besides many other applications, this solvent is used as entrainer for the separation of waterethanol mixtures by means of extractive distillation [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…or branched), ethers and esters. As already mentioned by other authors (Gui et al, 2011;Kazarian et al, 1996;Nelson and Borkman, 1998), the esters oxygen and the ether oxygen provide favorable interaction sites for CO 2 and qualify members of these chemical families as good solvents for the physical absorption of CO 2 . We should note, however, that our method currently does not distinguish between isomers.…”
Section: Tablementioning
confidence: 57%
“…The result also fitted the results presented in other literatures well. 21 Diffusivity of CO 2 in EG solution at 298 K was estimated with the aid of literature data and a semiempirical Stokes-Einstein relation. Oyevaar et al derived a modified Stokes-Einstein relation as shown in Eq.…”
Section: Physical Propertiesmentioning
confidence: 99%